Potentials of climate emergency declarations for degrowth transformations: The ambivalent stance of German municipalities in conflicts over a post-fossil future; Das Potenzial von Klimanotstandserklärungen für Transformationsbestrebungen in Richtung Postwachstumsgesellschaft: Die ambivalente Rolle deutscher Kommunen in Konflikten um eine postfossile Zukunft - Anton Brokow-Loga; Timmo Krüger (Raumforschung und Raumordnung / Spatial Research and Planning, 2023)
This paper addresses the scope for action by municipalities in a climate emergency and places it in the framework of ecomodern (urban) policy. We analyse the way in which two German 'climate emergency municipalities' translate conflicts of post-fossil transformation into concrete political and planning strategies. Although more than 2,200 authorities around the world have already declared a climate emergency, research on the impact of these resolutions on the political orientation of municipalities is very limited. Our research focus is on the (potentially agonistic) treatment of conflicts in planning. We argue that in times of a socio-ecological crisis, success in conflict resolution cannot refer to appeasement and depoliticisation. Instead, we propose a framework of five criteria, based on critical theory on ecomodern strategies, planning processes and degrowth. Thus, this practice-related and explorative paper connects empirical insights from the German cities of Constance and Berlin with an innovative normative framework. The findings tell a complex story of an, at least partial, admission of the failure of previous climate mitigation strategies, a lack of social institutions of limits, an instrumental relation to nature and a disregard for social injustices. The paper discusses how municipalities, in the context of ongoing tensions over the post-fossil transformation in Germany, on the one hand hold on to business-as-usual approaches, but on the other hand also set political impulses for change. – – In diesem Aufsatz diskutieren wir die Handlungsmöglichkeiten von Kommunen, die den Klimanotstand ausgerufen haben, vor dem Hintergrund der Dominanz ökomoderner (Stadt-)Politik. Wir analysieren, wie zwei deutsche ,Klimanotstandskommunen' Konflikte um die postfossile Transformation in konkrete politische und planerische Strategien umsetzen. Obwohl weltweit bereits mehr als 2.200 Städte und Gemeinden den Klimanotstand ausgerufen haben, gibt es bislang nur sehr wenige Untersuchungen zu den Auswirkungen dieser Beschlüsse auf die politische Ausrichtung der Kommunen. Unser Forschungsschwerpunkt bezieht sich auf die (potenziell agonistische) Bearbeitung von Konflikten in der Planung. In Zeiten einer sozialökologischen Krise ist eine Konfliktlösung, die auf Appeasement und Entpolitisierung basiert, nicht als Erfolg anzusehen. Stattdessen schlagen wir einen Orientierungsrahmen vor, dessen fünf Kriterien wir in der Auseinandersetzung mit kritischen Perspektiven auf ökomoderne Strategien, Planungsprozesse und Postwachstum erarbeitet haben. Dementsprechend verbindet unser praxisbezogener und explorativer Beitrag empirische Erkenntnisse aus den deutschen Städten Konstanz und Berlin mit einem innovativen normativen Orientierungsrahmen. Unsere Forschungsergebnisse erzählen eine komplexe Geschichte von einem zumindest teilweisen Eingeständnis des Scheiterns bisheriger Klimaschutzstrategien, einem Mangel an gesellschaftlichen Institutionen der Selbstbegrenzung, einem instrumentellen Verhältnis zur Natur und einer Vernachlässigung sozialer Ungerechtigkeiten. Im Aufsatz arbeiten wir heraus, wie Kommunen im Kontext aktueller Konflikte um die postfossile Transformationin Deutschland einerseits an Business-as-usual-Ansätzen festhalten, andererseits aber auch politische Impulse für Veränderungen setzen.
Keywords: 710; Degrowth; climate emergency; municipalities; conflicts; post-fossil transformations; Postwachstum; Klimanotstand; Kommunen; Konflikte; postfossile Transformation